Antioxidant Protection of Donor Packed Red Blood Cells using Mexidol - Gavryuchenkov D.V.; Fedoseykin I.V.; Kosachev V.E.; Shapovalova V.A.; Dinov E.N.; Dinova Y.E.; Nikiforov I.A.; Merkin A.G. (Journal of Antioxidant Activity, 2018)
The current research shows the possibility of long-term conservation of the erythrocytes an-tioxidant activity in the process of donor packed red blood cells while introducing mexidol to the hemoconservant glugicir composition.
Keywords: hemoconservants